2019
DOI: 10.3390/app9235252
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Advanced Consolidants for the Application on Sandstone

Abstract: Alkoxy-based consolidants are widely used for conservation of cultural heritage objects made from sandstones. Even if such consolidants were introduced into practice already in the 19th century, their performance has been enhanced by several modifications to their composition only recently. To obtain a relevant comparison of their application potential, both commercial (Remmers KSE OH and SurfaPore FX SB) and a self-developed particle-modified ethyl silicate consolidant supplemented with two phosphate-based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Depending on the gel deposition rate and the deposited amount of gel in sandstone pores, the strength increase was different for KSE 100, KSE 300, and KSE 510 [38]. Modified silica acid esters seem to perform well on low strength sandstone, too [28]. This research on porous limestone consolidation is in line with previous works [23].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Depending on the gel deposition rate and the deposited amount of gel in sandstone pores, the strength increase was different for KSE 100, KSE 300, and KSE 510 [38]. Modified silica acid esters seem to perform well on low strength sandstone, too [28]. This research on porous limestone consolidation is in line with previous works [23].…”
Section: Discussionsupporting
confidence: 88%
“…In our test, we used silica acid esters. The selection of the four tested materials is justified since these are the most commonly used consolidants in Hungary and commonly applied worldwide [26] for stones other than limestone, such as sandstone [27,28] or volcanic tuffs [29]. For limestone, silica acid esters are also used but in recent years, studies dealing with nano-lime treatment are also known [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…We refer to rock consolidation as the strengthening of rocks by the generation of new chemical bonds between the rock grains. Alkoxysilane [Si­(OR) 4 ] products are among the most applied rock consolidants, proving efficient in sandstone grain gluing . The consolidation by these chemicals is based on the formation of amorphous silica in the rock during hydrolysis–condensation reactions .…”
Section: Consolidating Agentsmentioning
confidence: 99%
“…In contrast, Graziani et al tested (applied by brushing) a mixture of TEOS with two organic bases (white spirit and isopropyl alcohol) and increased Giallo Siena and Globigerina limestone specimens’ tensile strength and dynamic modulus by 126% and 63%, respectively . Despite the consolidation efficiency of alkoxysilane products, they have several drawbacks, such as the hydrophobicity effect that lingers for a couple of months, extended curing periods which may last up to a month, and the tendency to crack with aging. ,, Moreover, Sassoni et al observed a pronounced decrease in porosity (up to 62.6%) and impairment of water sorption abilities of the rocks that were treated with TEOS . The same observations were confirmed by Graziani et al…”
Section: Consolidating Agentsmentioning
confidence: 99%
See 1 more Smart Citation